2020
DOI: 10.3389/fnins.2020.00256
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Amyloid Pathways: A Mechanistic Approach to Etiology

Abstract: Amyloids are fibrillar protein aggregates associated with diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), type II diabetes and Creutzfeldt-Jakob disease. The process of amyloid polymerization involves three pathological protein transformations; from natively folded conformation to the cross-β conformation, from biophysically soluble to insoluble, and from biologically functional to non-functional. While amyloids share a similar cross-β conformation, the biophysical transformation can eithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 122 publications
0
25
0
Order By: Relevance
“…Also, when using only data from the [18] F-florbetapir and excluding subjects within 5% of the threshold in both tracers the results were unchanged. This limitation is attenuated by the fact that Ab40 is less fibrillogenic than Ab42 in CSF, rendering it less relevant for the study of brain amyloidosis [2]. Finally, although the findings obtained in this study were based on robust statistical and sensitivity analyses, they did not come from a "perfect" study, which would have directly measured soluble Ab42 in the brain, with such techniques as microdialysis or fresh-frozen brain tissue biopsies, and corrected for the number of active neurons, the volume and flow rate of CSF, and the presence of other brain pathologies to understand the influence of local levels of Ab42 in brain tissues and the influence of neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, when using only data from the [18] F-florbetapir and excluding subjects within 5% of the threshold in both tracers the results were unchanged. This limitation is attenuated by the fact that Ab40 is less fibrillogenic than Ab42 in CSF, rendering it less relevant for the study of brain amyloidosis [2]. Finally, although the findings obtained in this study were based on robust statistical and sensitivity analyses, they did not come from a "perfect" study, which would have directly measured soluble Ab42 in the brain, with such techniques as microdialysis or fresh-frozen brain tissue biopsies, and corrected for the number of active neurons, the volume and flow rate of CSF, and the presence of other brain pathologies to understand the influence of local levels of Ab42 in brain tissues and the influence of neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This toxic gain-of-function hypothesis must be counterbalanced by the loss of normal proteins when undergoing aggregation. Proteins and peptides carry out their normal functions in the soluble state; misfolding into insoluble fibers with the characteristic cross-β conformation, known as amyloids, renders them non-functional [ 2 ]. Examples of loss of function of normal proteins when transformed into amyloids include loss of glycemic control in insulin-derived amyloidosis and loss of p53 tumor suppression function in TP53 mutations [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses were shown to attract protein coronae when introduced into various biological fluids, such as human plasma or human bronchoalveolar lavage fluid [ 48 ]. Interestingly, the viruses also seemed to accelerate the aggregation of Aβ into amyloid, which suggest a potential role of heterogenous nucleation in amyloid diseases [ 49 ]. In another study, we demonstrated that pre-fibrillar Aβ aggregates (protofibrils) attract a range of different proteins when exposed to human serum or CSF [ 50 ].…”
Section: Bottom-up Approaches To Identify Interaction Partners Of Amyloidmentioning
confidence: 99%
“…Unfortunately, we were unable to study the deceased maternal grandmother or her healthy siblings to evaluate for TGM6 carrier status. We also acknowledge that a single case study cannot address the wider question of whether the pathogenetic mechanisms of tau proteinopathies are associated with normal tau depletion (loss-of-function model) [ 24 ] or abnormal tau accumulation (gain-of-function model), and the extent to which either or both of these contribute to the underlying clinical phenotype [ 25 ]. Further in vivo studies on mouse models will be needed to clarify the interaction between TGM6 and tau pathology.…”
Section: Discussionmentioning
confidence: 99%